Editorial: Making Unstructured Abstracts More Concrete - Dobbins, Kerry; Pollard, Eileen; Andrew, Martin; Middleton, Rebekkah (Journal of University Teaching and Learning Practice, 2024)
The objective of this editorial is two-fold. First, to place the importance of clear abstract writing in the context of booming academic submissions. The editorial highlights the huge pressure on systems of review that have had the side effect of strongly positioning the abstract as gatekeeper to publication. Such emphasis on this short, hardworking text means that if the abstract is poorly written or does not effectively articulate its contribution to pedagogy, it falls at the first hurdle. Second, the editorial aims to give practical advice to scholars seeking publication of their learning and teaching research and scholarship by emphasizing the centrality of meaningful contribution at the heart of good research design, which is then further distilled into an articulate abstract. Not what was done, but what was found: the contribution of the contribution. Furthermore, the authors are aware of, and sensitive to, the many voices historically excluded from discussions of higher education and therefore also wish this editorial to act as an enabler for those researchers. As such, the editorial simply offers principles of effective abstract writing to ensure openness to different approaches and styles, resisting an abstract-formula beyond placing the meaningful contribution front-and-centre. On a meta level, this abstract attempts to articulate its meaningful contribution to the debate, by following these principles, while crucially retaining the voice and character of its authors.